1998
DOI: 10.1007/bf02678551
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin’s disease: A disorder of dysregulated cellular cross-talk

Abstract: Hodgkin's disease (HD) is a peculiar type of human malignant lymphoma characterized by a very low frequency of tumor cells, the so called Hodgkin and Reed-Sternberg (H-RS) cells, embedded in a hyperplastic background of non-neoplastic (reactive) cells recruited and activated by H-RS cells-derived cytokines. H-RS cells can be functionally regarded as antigen-presenting cells (APC) able to elicit an intense, but anergic and ineffective, T-cell mediated immune response along with a hyperplastic inflammatory react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 83 publications
0
27
0
Order By: Relevance
“…development of this malignancy is not fully understood, it is supposed that EBV rescues from apoptosis those B lymphocytes whose differentiation is faulty, probably by means of proliferative and antiapoptotic signals (22,29). The resemblance described for LMP1 variants among EBVrelated lymphomas and IM were made more evident when genomic arrangements, including EBNA3C, EBNA1, and BZLF1 along with LMP1 variants, were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…development of this malignancy is not fully understood, it is supposed that EBV rescues from apoptosis those B lymphocytes whose differentiation is faulty, probably by means of proliferative and antiapoptotic signals (22,29). The resemblance described for LMP1 variants among EBVrelated lymphomas and IM were made more evident when genomic arrangements, including EBNA3C, EBNA1, and BZLF1 along with LMP1 variants, were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…their reactive neighboring cells are able to cross-talk through a complex network of cytokine-dependent and cell contact-dependent interactions. As a result of such interactions, mediated by specific surface receptors and adhesion molecules on both tumor and nonneoplastic cells, cHL cells may receive several proliferative and antiapoptotic signals, favoring the cellular expansion and tumor cell survival in cHL [22,23]. In a recent study by Tzankov et al [24], it was shown that 90% of the cHL cells were positive for proliferative cell nuclear antigen and 98% were positive for cyclin A.…”
Section: Discussionmentioning
confidence: 96%
“…8,9,13,25,26 Both mast cells and eosinophils are implicated in the stimulation of HRS cells, 4,18 and the number of these cell types in affected lymph nodes correlates with poor prognosis. [27][28][29] Thus, IL-9 may be of importance in HL development, regulating both HRS cells as well as infiltrating cells.…”
Section: Figurementioning
confidence: 99%
“…1,2 These different cytokines may also be responsible for sclerosis, tissue eosinophilia and the B-symptoms -night sweats, fever and weight loss -seen in many HL patients. 3,4 One cytokine associated with HL is interleukin-9 (IL-9). 5 This is a multifunctional cytokine mainly produced by stimulated T H 2-cells, first described to allow antigen-independent proliferation of murine T-helper cell clones, 6 and enhance proliferation in murine mast cell lines.…”
Section: Introductionmentioning
confidence: 99%